EPTRI - European Paediatric Translational Research Infrastructure. Bridging the gaps of the paediatric excellence medicine - Donato Bonifazi; Mariangela Lupo; Valeria Pignataro; Irmgard Toni; Hana Kubova; Catherine Tuleu; Marialuisa Lavitrano; Adriana Ceci (University of Huddersfield Press, 2019)
Development of age appropriate medicines for children is one of the major challenge of our century. Historically, research of new paediatric drugs has been neglected due to poor industrial interest and limited public and private investments. The ID-EPTRI project is aimed to bridge the existing gaps in the paediatric medicine that stop the progress, from the early stage drug development phases to be translated into paediatric use of medicines, through a new paediatric Research Infrastructure. To reach this goal, EPTRI has developed and disseminated a survey in order to identify the gaps and map the competences of the excellence of the paediatric research in pan-European countries that will be the potential service providers of the new Research Infrastructure. EPTRI will network all the available competences and technologies useful to the paediatric research, creating an open science space allowing top-level researchers to work together.